Existence of stationary solutions for an isothermal compressible flow - Santaria Leuyacc, Yony Raúl (2020)
In this work we are interested in studying the existence of stationary solutions for a Navier--Stokes--3D equation in a compressible and isothermal flow. In order to prove the existence of solutions we use a method of successive approximations, following the results shown by M. Padula.